The Effect of Moringa Leaf Extract (Moringa oleifera L) as Feed Additive in Drinking Water on Growth Performance and Percentage of Broiler Internal Organs: Pengaruh Pemberian Ekstrak Daun Kelor (Moringa oleifera L) sebagai Feed Additive dalam Air Minum terhadap Performa Pertumbuhan dan Persentase Organ dalam Broiler - Fenita, Yosi; Kaharuddin, Desia; Nurmeiliasari, Nurmeiliasari; Azis, Arif Rahman; Kumalasari, Widia (Buletin Peternakan Tropis, 2024)
This study aims to evaluate the impact of giving 70% ethanol extract of Moringa leaves as a feed additive in drinking water on growth performance and percentage of internal organs in broilers. The design applied was a completely randomized design (CRD) with four treatments and five replicates, where each replicate consisted of eight broilers. The treatments given varied in the levels of moringa leaf extract in drinking water, namely: P0 (drinking water without moringa leaf extract), P1 (0.45 g moringa leaf extract in 1 liter of drinking water), P2 (0.9 g moringa leaf extract in 1 liter of drinking water), and P3 (1.35 g moringa leaf extract in 1 liter of drinking water). The observed variables included ration consumption, body weight gain, final weight, ration conversion, as well as the percentage and weight of internal organs such as liver, heart, intestine, and cecum length and percentage. The results showed that the provision of moringa leaf extract at various doses had no significant effect (P > 0.05) on ration consumption, body weight gain, final weight, ration conversion, percentage and weight of liver, heart weight, intestinal weight, intestinal length, or percentage and length of broiler cecum. Based on these results, it can be concluded that the provision of Moringa leaf extract in drinking water at doses of 0.45 g to 1.35 g does not have a significant impact on the performance of growth and internal organs of broilers.